Influence of Transverse Cross‐Phases on Propagations of Optical Beams in Linear and Nonlinear Regimes. Issue 12 (19th October 2020) - Liang, Guo; Zhang, Huicong; Fang, Lei; Shou, Qian; Hu, Wei; Guo, Qi
Abstract: It is predicted that an orbital angular momentum (OAM) carried by an elliptic Gaussian beam (EGB) with a cross‐phase can induce an effective anisotropic diffraction (AD). At the so‐called critical OAM, such an OAM‐induced AD makes the spiraling elliptic Gaussian mode, which expands owing to the diffraction while keeping its elliptic degree changeless, exist in linearly isotropic media, where only the circular Gaussian mode is supposed to exist for a beam without an OAM. In this study, such a phenomenon is experimentally demonstrated via the propagations of the EGBs with the OAM in linearly and both‐linearly‐and‐nonlinearly isotropic media. In the former case, the spiraling elliptic Gaussian mode is observed at the critical OAM in the free space. In the latter case, the spiraling elliptic soliton predicted by Desyatnikov et al. is observed for the first time in cylindrical lead glass. The physics behind the spiraling elliptic soliton is the OAM‐induced AD, which preserves the elliptic degree of the EGB, whereas the nonlinearity only balances the diffraction of the EGB. The OAM‐induced AD is just a linear effect and has nothing to do with nonlinearity. Abstract : Orbital angular momentum (OAM) carried by an elliptic Gaussian beam (EGB) with a cross‐phase can induce an effective anisotropic diffraction. Such a phenomenon is experimentally demonstrated via propagations of the EGBs with OAM in linearly and both‐linearly‐and‐nonlinearly isotropic media. In linear and nonlinear regimes, spiraling elliptic Gaussian modes and spiraling elliptic solitons are observed, respectively.